The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5038/2640-6489.4.2.1066
|View full text |Cite
|
Sign up to set email alerts
|

The impact of burnout on organizational commitment: A study of public sector employees in Turkey

Abstract: This study investigates the relationship between burnout and organizational commitment. It tests the relationship using a sample of 700 public officers in Istanbul by using structural equation modeling. The model tested via partial least squares method via SmartPls software. Results have shown that employees' burnout are negatively related to organizational commitment. Specifically, while emotional exhaustion is negatively related to commitment, personal accomplishment contributes positively to commitment. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 72 publications
1
8
0
3
Order By: Relevance
“…As part of the coping process, these individuals may want to escape their dire situation and develop a desire to leave the organization. Previous variable-centered studies confirmed the positive relationship between burnout and psychological distress (De Beer, 2021) and turnover intention and the negative relationship between burnout and affective commitment (Sarisik et al, 2019).…”
Section: Psychological Distress Affective Organizational Commitment A...mentioning
confidence: 66%
“…As part of the coping process, these individuals may want to escape their dire situation and develop a desire to leave the organization. Previous variable-centered studies confirmed the positive relationship between burnout and psychological distress (De Beer, 2021) and turnover intention and the negative relationship between burnout and affective commitment (Sarisik et al, 2019).…”
Section: Psychological Distress Affective Organizational Commitment A...mentioning
confidence: 66%
“…It is characterized to affect employees of the service sector such as teachers, police, nurses, doctors, etc. (Sarisik et al, 2019 ). The World Health Organization, following the International Classification of Disease (ICD) 11, defines burnout as a result of chronic workplace stress that the employees cannot manage (World Health Organization, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Abundant previous studies were found on the antecedents of employees' OC in various contexts (Lambert et al, 2018;Luz et al, 2018;Pathak & Tripathi, 2010;Top et al, 2015). Several variables received great attention from previous researchers, such as different leadership styles (Chen et al, 2019;Choi et al, 2015b;Gul et al, 2012), employees' burnout (Sarisik et al, 2019), job related variables like job security and work style (Pathak & Tripathi, 2010;Spanuth & Wald, 2017), job characters (Coetzer & Rothmann, 2006), employee training and teamwork (Hanaysha, 2016a), environment and organizational learning (Hanaysha, 2016b), psychosocial safety climate (Geisler et al, 2019), corporate values, and corporate social responsibility (Asrar-ul-Haq et al, 2017;Obalola et al, 2012). However, few studies probe deeply into the impact of ethics variables on OC of employees in Chinese context where employees and managers may confront different ethical situations from other countries.…”
Section: Introductionmentioning
confidence: 99%